Synthesis of 2-Phenylimino-3-Phenyl Thiazolidine Δ2-2-Thio-6-p-Methoxy Phenyl (4,5-d)-Pyrimidine - Kumar, Birendra; Kumar, Ashok; kumar, Shashi (Asian Journal of Chemistry, 2010)
In the present communication the authors describe the synthesis and characterization of 2-phenylimino-3-phenyl thiazolidin Δ2-2- thio-6-p-methoxy phenyl (4,5-d) pyrimidine.